MODIFICATION OF THEORY OF PLANNED BEHAVIOR TO MEASURE THE INTENTIONS AND BEHAVIOR OF PEOPLES PARTICIPATION IN THE WASTE BANK PROGRAM (CASE: BANTUL REGENCY) - Anggun Nindy Fatliana; Naniek Utami Handayani; Manik Mahacandra; Utaminingsih Linarti (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
Waste is an environmental problem that hasn’t been resolved until now. This problem can be overcome with the waste bank program. The success of the waste bank is supported by the high level of community participation. Currently, the level of community participation in Bantul Regency is still low, which is below 50%. The purpose of this research is to investigates what factors that can increase people’s intention and behavior of participating in waste bank activities at Bantul Regency. This research using factors from Theory of Planned Behavior (TPB) model. Besides of factors from Theory of Planned Behavior this research added other factors like knowledge of how and what, knowledge of the consequences and situational factors used as a measurement tools. The research used 300 samples. The target respondents for this research are members who actively participate in the waste bank activities. The sampling technique is purposive sampling, regression analysis methods is using on this research. The analysis results showed that attitudes, subjective norms, knowledge of how and what, knowledge of consequence and situational factor have a significant effect on the people’s intention to participate in the waste bank programs. Meanwhile the perceived control behavior variable has no significant effect on the people’s intention to participate in the waste bank program. All the factors togethers can explain the intention of 44.7%.